Basic Education Learning Continuity Plan (BE-LCP) Implementation: Challenges and Opportunities - Sabacajan, Bazil T.; Moradods, Alexander N. (Future Science / FSH-PH Publications, 2023)
The Basic Education Learning Continuity Plan (BE-LCP) was developed collaboratively by the Philippines through the Department of Education) in response to the need to continue education despite the restrictions imposed by the COVID-19 crisis. This is to ensure that education is delivered without jeopardizing the health and safety of its learners and employees. Therefore, this current study aims to determine the level of awareness and the extent of challenges and opportunities in implementing the Basic Education Learning Continuity Plan. The study was mainly quantitative by design and used the survey questionnaire and interview method to gather the necessary information. The survey questionnaire served as primary data from respondents' responses on the awareness, challenges, and opportunities of BE- LCP implementation. The result of the study indicates that the overall level of BE-LCP awareness was placed at a moderate extent, the overall extent of challenges among the respondents was penned moderate, and the overall extent of opportunities on the implementation of the BE-LCP was also moderate. Furthermore, there was a significant difference in the level of awareness on the BE-LCP implementation among the teachers, stakeholders, and students, meanwhile, the study reveals that there was no significant relationship among the variables of the study. As a result, the Division of Camiguin intends to ensure BE-LCP implementation and deliver quality education in the new normal.